2021
DOI: 10.3390/app11167717
|View full text |Cite
|
Sign up to set email alerts
|

Wind Characteristics in Mountainous Valleys Obtained through Field Measurement

Abstract: The wind characteristics of the mountainous environment in Western China are extremely complex. Many advances have occurred in the study of wind characteristics in plains or hilly areas. However, some limitations remain in the study of mountain passes and riverbanks. We selected a mountain pass and river beach in a certain area as the research objects, then set up observation instruments at different locations to establish temporary observation stations to collect more than one year of measured data. By proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 34 publications
(37 reference statements)
0
5
0
Order By: Relevance
“…Considering the terrain and climate features of the valley, the oncoming wind direction at the bridge site may be related to the valley extension direction and the dominant wind directions [1,2,17], so three directions along the extension of the valley and two dominant wind directions were designed: 102 • , 211 • , 326 • , 90 • , and 270 • , as shown in Figure 1a. The surface roughness was set as 0.12 m, and the class C wind speed profile was set at the entrance.…”
Section: Oncoming Wind Directionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the terrain and climate features of the valley, the oncoming wind direction at the bridge site may be related to the valley extension direction and the dominant wind directions [1,2,17], so three directions along the extension of the valley and two dominant wind directions were designed: 102 • , 211 • , 326 • , 90 • , and 270 • , as shown in Figure 1a. The surface roughness was set as 0.12 m, and the class C wind speed profile was set at the entrance.…”
Section: Oncoming Wind Directionmentioning
confidence: 99%
“…Research on the wind characteristics of a valley is mainly based on field measurements [1,2], wind tunnel tests [3], and numerical simulations. Although field measurement can directly obtain the wind parameter data at the measured position, it is time-consuming, labor-intensive, and requires huge investment, and the obtained wind parameters are limited in quantity, time, and space.…”
Section: Introductionmentioning
confidence: 99%
“…The test results in wind tunnels show that the mean wind speed profile in canyons changes along the bridge span, and it cannot be simulated as a uniform wind speed profile [25]. Wind tunnel tests in mountainous canyons require the production of huge site models, the geographical range expressed by the terrain model and the scale adopted are generally small [26]. Some studies have found that as the scale decreases, modeling of complex terrain tends to have greater deviation [27].…”
Section: Introductionmentioning
confidence: 99%
“…Field measurement, wind tunnel test (WTT), and computational fluid dynamics (CFD) numerical simulation are conventional research methods in structural wind engineering [1,2]. WTT can study the interaction between the model with a certain scale ratio and the simulated gas flow, and the numerical simulation can observe the gas flow globally at full scale and provide the entire flow field data.…”
Section: Introductionmentioning
confidence: 99%